Type II choledochal cyst of the cystic duct in a 3 Month old - Jana DeJesus; Byron Hughes; Emily Geisler; Christine Defilippo; Jaclyn Gaffey; Ravi S. Radhakrishnan (Elsevier, 2022)
Type II choledochal cysts are rare, representing approximately 2% of cases [1-3]. Even fewer cases of type II cysts involving the cystic duct have been reported. Excision is necessary to prevent future ascending cholangitis, liver fibrosis, and malignancy [1-3, 5]. We present a case of a 3 month old male born premature who presented with persistent conjugated hyperbilirubinemia. Imaging workup demonstrated a cystic structure at the neck of the cystic duct, measuring 0.9 cm × 1.6 cm x 0.9 cm. Delayed biliary excretion was noted on HIDA. Decision was made to take the patient to the operating room for a cholecystectomy and intraoperative cholangiogram to delineate the anatomy. Intraoperatively, the patient was found to have a small cystic structure arising from the cystic duct. A cholecystectomy was performed and the patient recovered well. Choledochal cysts of the cystic duct are considered type II cysts based on the original Todani Classification. Due to their location, cholecystectomy is required during excision [1-3,5]. Wide-based cysts involving the common bile duct additionally require hepaticojejunostomy [1-3,5].